(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1999)
A biostratigraphic scheme for the Triassic pelagic sediments in Albania, based on the distribution of conodonts, is presented for the first time. The investigated series range from Late Olenekian (Spathian) to the Norian or Early Rhaethian. The lowest Spathian level contains Neospathodus waageni, N. triangularis and N. homeri. The Aegean (Lower Anisian) is characterized by Chiosella timorensis, the Pelsonian (Upper Anisian) by Pararagondelolla. bulgarica and the presence of Nicoraella kokaeli, whereas the Late Anisian to Early Ladinian transition remains problematic, the Illyrian being documented by the presence of Paragondolella bifurcata only, Paragondolella exelsa morphotypes and the P. cornuta-constricta complex being considered Fassanian, the upper part of the Langobardian (Late Ladinian) being well documented by Sephardiella diedeli and S. mostleri. The Carnian with Paragondolella. polygnathiformis and P. auriformis is followed most Norian conodont levels from Ancyrogondolella primitia to E. bidentata. The Uppermost Norian - Rhaetian boundary is verified by the presence of Misikella hernsteini, associated with Epigondolella slovakensis. Conodont associations provide a biostratigraphic scheme of the Triassic pelagic facies for each tectonic zone of Albania.